Body - Language - Communication : an international handbook on multimodality in human interaction. - Müller, Cornelia, 1960-; Cienki, Alan J., 1959-; Fricke, Ellen, 1964-; Ladewig, Silva H., 1978-; McNeill, David; Teßendorf, Sedinha (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2013)
Volume I of the handbook presents contemporary, multidisciplinary, historical, theoretical, and methodological aspects of how body movements relate to language. It documents how leading scholars from differenct disciplinary backgrounds conceptualize and analyze this complex relationship. Five chapters and a total of 72 articles, present current and past approaches, including multidisciplinary methods of analysis.